Splošen koncept načrtovanja testnih primerov - Dogša, Tomaž (Uporabna informatika (Ljubljana), 2001)
An effective testing reduces teh costs of development and maintenance. At the same time it enables an objective view on software quality. In this paper we shall describe the general concepts of test case design based on testing models. We have illustrated this with two simple and most widely used strategies.
Keywords: preizkušanje; programska oprema; testiranje